Confounding of cerebral blood flow velocity by blood pressure during breath-holding or hyperventilation in TIA or stroke - Webb, A; Paolucci, M; Mazzucco, S; Li, L; Rothwell, P (American Heart Association, 2019)
Background and Purpose: Breath-holding (BH) and hyperventilation (HV) are used to assess abnormal cerebrovascular reactivity (CVR), often in relation to severity of small vessel disease and risk of stroke with carotid stenosis, but responses may be confounded by blood pressure (BP) changes. We compared effects of BP and end-tidal CO2 (etCO2) on middle cerebral artery mean flow velocity (MFV) in consecutive TIA and minor stroke patients. Methods: In the population-based, prospective, Oxford Vascular Study (OXVASC) Phenotyped cohort, change in MFV on transcranial Doppler ultrasound (∆MFV, DWL-DopplerBox), beat-to-beat BP (Finometer) and etCO2 were measured during 30 seconds BH or HV. Two blinded reviewers independently assessed recording quality. Dependence of ∆MFV on ∆BP and ∆etCO2 were determined by general linear models, stratified by quartiles. Results: 488/602 (81%) patients with adequate bone windows had high quality recordings, more often in younger participants (64.6 vs 68.7 years, p<0.01), whilst 426 had hyperventilation tests (70.7%). During breath-holding, ∆MFV was correlated with a rise in MBP (r2=0.15, p<0.001) but not ∆CO2 (r2=0.002, p=0.32), except in patients with ∆MBP<10% (r2=0.13, p<0.001). In contrast during HV, the fall in MFV was similarly correlated with reduction in CO2 and reduction in MBP (∆CO2: r2=0.13, p<0.001; ∆MBP: r2=0.12, p<0.001), with a slightly greater effect of ∆CO2 when ∆MBP<10% (r2=0.15). Stratifying by quartile, MFV increased linearly during BH across quartiles of ∆MBP, with no increase with ∆etCO2. In contrast, during HV, MFV decreased linearly with ∆etCO2, independent of ∆MBP. Conclusions: In older patients with recent TIA or minor stroke, cerebral blood flow responses to breath-holding were confounded by BP changes, but reflected etCO2 change during hyperventilation. Correct interpretation of CVR responses to etCO2, including in small vessel disease and carotid stenosis, requires concurrent blood pressure measurement.